Promoting Inclusion Through Evidence-Based Alternatives to Restraint and Seclusion. (June 2017) - Trader, Barbara; Stonemeier, Jennifer; Berg, Tricia; Knowles, Christen; Massar, Michelle; Monzalve, Manuel; Pinkelman, Sarah; Nese, Rhonda; Ruppert, Traci; Horner, Robert
The use of restraint and seclusion in schools has been identified repeatedly as an approach that is overused, misused, and potentially dangerous. In this article, we emphasize the importance of an approach to supporting students with significant problem behavior that focuses on prevention, evidence-based intervention procedures, heightened levels of monitoring, and documented professional development. While the need for the use of restraint in emergency conditions will remain, the overall rate at which restraint and seclusion are used needs to be reduced and the quality of support for students with significant problem behavior needs to improve. An example of one district that is adopting a comprehensive alternative approach is provided.